230k views
0 votes
Find an expression which represents the sum of (4x + 1) and (-9x + 6) in

simplest terms.

User Austin Lin
by
4.6k points

1 Answer

4 votes

Answer:


-5x+7

Explanation:

Given: Two expressions are
(4x+1),(-9x+6)

To find: sum of the given expressions in simplest terms

Solution:

A variable is a term that takes various numerical values and a constant is a term that takes a fixed numerical value.

Consider
(4x+1)+(-9x+6)

Here, solve
(4x-9x),(1+6)


4x-9x=(4-9)x=-5x\\1+6=7

Therefore,


(4x+1)+(-9x+6)=(4x-9x)+(1+6)=-5x+7

User Kavet Kerek
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.